Optimization of the Role of Waqf Bank Micro in Access to Financing, Developing Human Resources Skills, and Financial Literacy on MSME Performance to Improve MSME’s Capital in Surabaya - Diana Mukhbitah Sary; Tri Andjarwati; Riyadi Nugroho (International Forum of Researchers and Lecturers, 2025)
Study This analyze the role of Waqf Bank Micro (BWM) in increase performance of MSMEs in Surabaya, with capitalization as variable mediation . Focus main covers access financing , human resource development, and literacy finance, using approach quantitative through survey against 90 MSME actors fostered by BWM Al- Fithrah Wava Mandiri . Analysis using SEM with SmartPLS 4.0 shows that third variable influential significant to performance of MSMEs, both in a way direct and through capitalization . Capitalization become the most dominant mediator ( coefficient 0.581; p-value 0.000). Findings This confirm role BWM doubles as institution financing and empowerment . In theoretical , results This support theory Resource-Based View (RBV) and its importance financing accompanied by strengthening capacity business in a way holistic.